(untitled) (Third Sector Social Economic Review, 2024)
The main purpose of this study is to contribute to the understanding of research trends in the field and to guide future research on the concept of sustainable fashion in literature by conducting a bibliometric analysis of studies on sustainable fashion in consumer behavior literature. In this study, where the quantitative research method was used, 663 studies in the Web of Science Core Collection database between 2001 and 2024 were examined using various statistical tools using the bibliometric analysis method. General information about studies, sources, countries, and authors was presented. Moreover, a word cloud, keyword co-occurrence network, thematic map, and trend topics by year were presented. The study found that sustainable fashion is frequently used in consumer behavior literature, especially after 2010. It was found that the most repeated words are ""consumption"", ""behavior"", ""consumer"", ""green"" and ""impact"". According to the co-occurrence analysis, the most frequently used keywords in publications are sustainability, sustainable fashion, fashion, fast fashion, slow fashion, and circular economy. It has been observed that decision-making, circular economy, and personal norms are among the trending research topics between 2022 and 2024. This research is instructive for textile industry specialists, academics, and engineers in terms of presenting the characteristics of sustainable fashion research from a comprehensive perspective. The findings of the study show that the importance of consumers’ attitudes and behaviors towards sustainable fashion is increasing. Therefore, it is suggested that sustainable fashion should be addressed by supporting it with different perspectives and themes in the consumer behavior literature for future research.